2013
DOI: 10.1016/j.amjmed.2013.09.002
|View full text |Cite
|
Sign up to set email alerts
|

Racial and Ethnic Disparities in Disease Activity in Patients with Rheumatoid Arthritis

Abstract: Background Observational studies of patients with rheumatoid arthritis have suggested that racial and ethnic disparities exist for minority populations. We compared disease activity and clinical outcomes across racial and ethnic groups using data from a large, contemporary United States registry. Methods We analyzed data from two time periods (2005-2007 and 2010-2012). The Clinical Disease Activity Index was examined as both a continuous measure and as dichotomous measures of disease activity states. Outcome… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

4
78
0
3

Year Published

2014
2014
2021
2021

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 103 publications
(85 citation statements)
references
References 20 publications
4
78
0
3
Order By: Relevance
“…[8][9][10] This disparity may lead to differences in such clinical outcomes as greater disease activity and lower remission rates in these patient subgroups. 11 Reduction in overall health services utilization costs through sustained remission in RA is well documented. 12 Therefore, from a payer's point of view, it is very important to understand and address potential disparities in the use of biologics among RA patients in order to control future health care costs.…”
Section: Patient Identification and Exclusion Criteriamentioning
confidence: 99%
“…[8][9][10] This disparity may lead to differences in such clinical outcomes as greater disease activity and lower remission rates in these patient subgroups. 11 Reduction in overall health services utilization costs through sustained remission in RA is well documented. 12 Therefore, from a payer's point of view, it is very important to understand and address potential disparities in the use of biologics among RA patients in order to control future health care costs.…”
Section: Patient Identification and Exclusion Criteriamentioning
confidence: 99%
“…Previous studies have shown that sociodemographic factors can affect multiple aspects of care in RA, including mortality and disability, disease activity, prevalence of comorbidities, patient‐reported outcomes, access to treatment/health services, treatment preferences and medication adherence, health literacy, and trust in providers . A better understanding of the effects of sociodemographic factors on the validity of PROMIS physical function measures will determine their generalizability across diverse communities.…”
Section: Introductionmentioning
confidence: 99%
“…We also found that African Americans were less likely to be on SC MTX than Caucasian patients. It has been previously shown that African American patients are less likely to be prescribed biologic agents than Caucasians and are also less likely to achieve clinical remission than Caucasian patients (24). However, it is unclear whether this is due to the fact that RA may be more aggressive in some ethnic groups, differences in patient preference regarding treatment, or some bias in prescribing (25)(26)(27).…”
Section: Resultsmentioning
confidence: 66%